State Purchasing Policy – A New Institution of Public Procurement Law - Czech, Ewa Katarzyna; Panasiuk, Andrzej (Review of European and Comparative Law, 2020)
The state's purchasing policy is one of the new institutions of the Public Procurement Law. Influenced by the changes in the package of directives coordinating public procurement procedures in 2014, our national legislator has taken steps to use public procurement for purposes other than strictly purchasing. Therefore, the authors' considerations strive to define the concept of "purchasing policy of the state", outlining the role and scope thereof in the functioning of the modern state. Furthermore, the authors try to point out problems related to its implementation by the public authorities, stating finally that purchasing policy will only be effectively implemented if all participants of the public procurement market are aware of the policy objectives.